Fast estimation of Speech Transmission Index using the Reverberation Time: Comparison between predictive equations for educational rooms of different sizes. (November 2018) - Leccese, Francesco; Rocca, Michele; Salvadori, Giacomo
Abstract: Ensuring a high speech intelligibility is an essential issue for educational rooms, especially in relation to the effectiveness of the student learning process. The Reverberation Time and the Speech Transmission Index are objective parameters commonly used to assess the acoustic quality of the rooms, according to their intended use. Especially the Speech Transmission Index can give interesting information about the speech intelligibility. As with the Reverberation Time, it would be very important to have simple equations aimed to the prediction of Speech Transmission Index values during the early design stage. There are different studies in the literature that propose equations, obtained on empirical basis, for a fast estimation of the Speech Transmission Index as a function of the Reverberation Time. In this paper, a comparison of the most significant equations proposed in the literature was done using the Reverberation Time and Speech Transmission Index values obtained from a measurement campaign at the School of Engineering of the University of Pisa on a sample of 11 educational rooms. The analysis was carried out for educational rooms of different sizes, in order to highlight differences in the prediction accuracy depending on the volume of the rooms. From the analysis results it was possible to highlight the equation that shows the best accuracy in predicting the experimental data for the sample of investigated rooms and propose, through a regression analysis, two new equations for the rapid estimation of the Speech Transmission Index.